UNSUR SOSIAL BUDAYA DALAM NOVEL BULAN TERBELAH DI LANGIT AMERIKA KARYA HANUM SALSABIELA RAIS DAN RANGGA ALMAHENDRA (KAJIAN SOSIOLOGI SASTRA) - Rina Pebriana; Arif Ardiansyah (Universitas PGRI Palembang, 2017)
This research was to describe the socio-cultural elements in the novel “BulanTerbelah di LangitAmerika” by HanumSalsabiela and RanggaAlmahendra. The significance of this research was to increase of knowledge in literary analysis and to assist the reader in expressing of meaning that contained in the novel by using socio-literary approach. The data of this research was taken by novel “BulanTerbelah di LangitAmerika” by HanumSalsabiela and RanggaAlmahendra. The method of this research was using qualitative method to obtain the socio-cultural element in the novel and the technique for collecting the data, the writer used content analysis. Based on the result of this research, the writer found that the novel describing socio-reality and becoming a document between socio-culture and western culture toward Muslim in America was being WTC among Islamophobia in America, tragedy of collapse of WTC building on September, 9th, 2001, social habitual in America and the historical facts of Islamic Civilization in America. Keywords: Socio-Cultural Elements, Novel “BulanTerbelah di Langit America” by HanumSalsabiela and RanggaAlmahendra